The Role of Islamic Boarding Schools in Instilling Deradicalization Values - Salman Alfarisi; Ikhwan Aziz Q; Khoiriyah Khoiriyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This research focuses on the ethics and morals of educators and learners in Islamic education. The ethics of educators and students in Islam turned out to be gradually starting to change, economic values gradually began to enter, so that what is happening now is that there are many problems that occur in the world of education such as the crisis of ethics from both educators and students. This study aims to examine how the ethics of educators and students in the perspective of Islamic education. The method in this research is a literature method that refers to books, esklopedia, and scientific articles. The conclusions in this study are the ethics that must be possessed by educators in the Islamic education perspective, including: teachers must have a broader understanding, be professional, love their students, provide the right to education in a fair, honest, sincere manner when dealing with diverse student situations. The ethics that must be possessed by peseta didik in the perspective of Islamic education are: having the intention to study because of Allah SWT, strong, sincere and steadfast in studying.